High temperature electrical transport study of Si-doped AlN. (October 2016) - Contreras, Sylvie; Konczewicz, Leszek; Ben Messaoud, Jaweb; Peyre, Hervé; Al Khalfioui, Mohamed; Matta, Samuel; Leroux, Mathieu; Damilano, Benjamin; Brault, Julien
Abstract: Electrical transport (resistivity and Hall Effect) have been studied in silicon doped aluminum nitride (AlN) thick epitaxial layers from 250 K up to 1000 K. The investigated samples, grown by molecular beam epitaxy were characterized by n-type conduction with an ambient temperature free carrier concentration of about ∼ 1 × 10 15  cm −3 . The donor level, situated about 250 meV below the conduction band edge, was found to be responsible for the experimentally observed increase of free carrier concentration with temperature. The temperature dependence of carrier mobility has been analyzed in the framework of a multimode scattering model. In the investigated samples the main scattering mechanism is supposed to be dislocation scattering. Highlights: High temperature Electrical transport in silicon doped aluminum nitride. The ionization energy of the donor level was found to be about 250 meV. Analyzing of temperature dependence of mobility using a multimode scattering model, including dislocation scattering.